TOEFL AND ART STUDENTS: BETWEEN ACADEMIC NECESSITY AND THE CHALLENGE OF A FOREIGN LANGUAGE - Helmi, Rahil; Payana, Wita Dwi; Anwar, Humaira; Yanti, Nurlayli; DE, Zuhrahmi (English Edu: Journal of English Teaching and Learning, 2025)
This study examines the intersection between institutional academic requirements and the linguistic challenges faced by undergraduate art students concerning the Test of English as a Foreign Language (TOEFL). In many Indonesian universities, TOEFL is mandated as a condition for graduation, positioning it as a vital component of academic success. However, for students in non-English disciplines, especially the arts, this requirement often poses a significant barrier due to limited exposure to English in their coursework. This research adopts a qualitative approach through semi-structured questionnaire and interviews with 43 art students to explore perceptions, preparation strategies, and motivational dynamics related to TOEFL. Using thematic analysis, key findings reveal that while students acknowledge the importance of TOEFL for future academic and professional opportunities, they frequently lack the necessary linguistic preparation, support, and test-taking strategies. Challenges such as inadequate vocabulary, low familiarity with standardized test formats, test-related anxiety, and limited integration of English in the art curriculum emerged prominently. Furthermore, the study identifies a predominance of extrinsic motivation such as graduation requirements and employment prospects rather than intrinsic interest in language mastery. These findings suggest a disconnect between institutional expectations and the lived academic experiences of art students. The study recommends incorporating English for Specific Purposes programs tailored to the arts, greater institutional support through preparatory workshops, and the integration of English into creative academic learning. Addressing these factors is crucial to enhancing both compliance with graduation standards and the development of functional English proficiency.